The impact of the flipped classroom strategy on developing the communication skills in classes among art education students - Malik Hamid Mohsen (الاكاديمي)
The technology and modern social communication medias have contributed to changing many of our concepts about education to a large extent; these technological advancements have created new challenges for the Instructor of course, but on the other hand it did provided him with expressive media, models and strategies that the old methods cannot fulfill, including the flipped classroom strategy, which is one of the modern technical solutions and in it's optimal use it can correct the weakness of the traditional education and can develop the communication skills as a whole among the students, in order to create a positive, active and interactive student. The current research contained - four chapters: the first one included the methodological framework represented by the aim of the study ((to know the impact of the flipped classroom strategy in developing class communication skills among students of art education)), the research included only the students of the fourth grade - Department of Art Education - the second semester For the year (2022_ 2023) - the subject of modern and contemporary art history - and the use of one of the means of social media communication (Telegram), and a zero hypothesis has been set for that. The second chapter include the literature review, focusing on two topics, the first is the definition of the flipped classroom strategy, while the second dealt with classroom communication skills. leading to the third chapter which is the research methods that include the presentation the sampling of the population and the the method of using educational video clips - in addition to the observation card - then the conducting of the research.The fourth chapter, includes the research results and their interpretation. The fifth provide the conclusions, recommendations and suggestions. Finally the research ended with a list of references